Screening and evaluation of cytotoxicity and antiviral effects of secondary metabolites from water extracts of Bersama abyssinica against SARS-CoV-2 Delta - Never Zekeya; Bertha Mamiro; Humphrey Ndossi; Rehema Chande Mallya; Mhuji Kilonzo; Alex Kisingo; Mkumbukwa Mtambo; Jafari Kideghesho; Jaffu Chilongola (BMC, 2022)
Abstract Background Bersama abyssinica is a common herb in Africa, with diverse medical uses in different areas. The plant is well-known in Tanzania for treating respiratory disorders such as TB, tonsillitis, bronchitis, and asthma, and it has lately been utilized to treat COVID-19 symptoms. Water extract of leaf and stem bark has been registered as an herbal medication known as 'Coviba Dawa' in Tanzania for the relief of bacterial respiratory infections. The extracts, however, have not been scientifically tested for their anti-viral activities. The aim of this work was to test for the cytotoxicity and antiviral effects of bioactive ingredients from B. abyssinica extracts against the Delta variant of the SARS-CoV-2 coronavirus. Methods B. abyssinica leaves and stem bark were dried under shade in room temperature and then pulverized to obtain small pieces before soaking into different solvents. One hundred grams of each, leaves and stem bark, were extracted in petroleum ether, dichloromethane, ethyl acetate and methanol. Water extract was obtained by decoction of stem bark and leaves into water. Phenols, flavonoids, tannins, and antioxidants were confirmed as components of the extracts. Analysis of polar extracts of bark stem bark and leaves was done. Antiviral screening and cytotoxicity experiments were conducted in a Biosafety Level 3 (BSL-3) Laboratory facility according to International Standard Operating Procedures (SOPs). Results By the use of LC-MS/MS analysis, this study confirmed the existence of four phenolic compounds in B. abyssinica water extract; 2,4-di-tert-butylphenol, 4-formyl-2-methoxyphenyl propionate, 7,8-Dihydroxy-4-methylcoumarin, and 2,3, 6-trimethoxyflavone with antioxidant activity. This study showed that, while the water extracts of B. abyssinica had significant antiviral activity against SARS Cov2 virus, it showed no cytotoxicity effect on Vero E6 cells. In particular, the water extract (Coviba dawa) showed 75% while ethylacetate fraction of B. abyssinica leaves showed a 50% in vitro viral inhibition, indicating that these substances may be useful for the development of future anti-viral agents. Conclusion We therefore recommend isolation of compounds for further profiling and development with a broader concentration range. We further recommend studies that determine the antiviral activity of extracts of B.abyssinica on other viral pathogens of clinical concern.